Storage Behaviour of Washed Mince from Pink Perch (Nemipterus japonicus) at -30oC - K., Rathnakumar; A., Jeyakumari; P., Velayutham (Fishery Technology, 2025)
The proximate composition of Pink perch (Nemipterus japonicus) used in the studywas recorded as protein, 16.22%; fat, 1.3% and ash, 1.7%. The yield of this fish after dressing ie., beheading and evisceration was 76%. The minced meat has a solubility of 91% and no TMA was recorded. Other physico-ejiemical properties also reflected its prime quality. The minced meat was frozen stored at -30oC. During storage up to 120 days ,slight pH increased up to 6%, a-amino nitrogen to 51% and TVB-N to 80%. However there was no significant change (P>0.05) in the FFA and PV during the storage period. Functional properties like solubility, viscosity, Ca2* ATfase activity did not vary significantly (P>0.05) with storage period indicating the quality of minced meat. The study indicateed that storage of minced meat of Pink perch (Nemipterus japonicus) at -30oC does not alter the’major protein fractions as indicated by the functional properties and gel forming ability. This was reflected in the over all acceptability of the cooked meat where, appearance and colour of meat did not vary significantly (P>0.05) with storage period.